PERAN GURU DALAM MENDIDIK SISWA PASCA PANDEMI COVID-19 DENGAN PERSPEKTIF PASTORAL KONSELING - Subaedah Luma; Inggrid C. Siwu; Randy A. A. P. Lombogia (POIMEN Jurnal Pastoral Konseling, 2022)
The purpose of this study is, to describe and analyze the learning process of teachers after the Covid-19 pandemic, as well as to analyze the obstacles and challenges of learning carried out by teachers in educating and educating students with a Pastoral Counseling perspective. The method used in this study is the Descriptive Qualitative method, which was implemented at one of the elementary schools in Manado City, in 2022. The data was collected through observations, interviews, and documentation studies. The results of the analysis and interpretation of this data, it is an indication that there are obstacles and challenges in the learning process that is, there are some students who have psychological symptoms and delays in understanding the lesson. From the findings of this research, it is recommended, that every teacher must always be creative, innovative, and understand his students in educating and implementing learning, and can continue to develop skills, create the new things in educating their students and always evaluate. Every teacher must also have five bits of intelligence that are intellectual, moral, social, emotional, and motor intelligence.